Validitas dan Reliabilitas Kuesioner Model Hot-Fit pada Penggunaan SIMRS - Widyaningrum, Mia Rachmi; Wiliyanarti, Pipit Festi; Samiyah, Mirrah (Journal of Telenursing (JOTING), 2025)
This study aims to test the validity and reliability of the questionnaire that can later be used to evaluate the hospital management information system (SIMRS) implementation in hospitals. This is a cross-sectional study with a questionnaire compiled in Indonesian based on the HOT-Fit theoretical framework. The results of the indicator relationship test that explains the latent variables as the model in the HOT-Fit theory show significant results on all of its constituent indicators. The statement regarding training related to SIMRS showed the lowest significance, namely p = 0.002 and loading factor <0.637. In conclusion, the SIMRS evaluation questionnaire with the HOT-Fit model is declared valid and reliable for evaluating SIMRS in hospitals. Keywords: Evaluation, SIM RS, HOT-FI Model